Gender Politics : Citizenship, Activism and Sexual Diversity. - Monro, Surya (Pluto Press, 2005)
Is it possible to move beyond the male-female gender binary system? What happens to gender theory when we consider sex and gender identities as more than just 'male' or 'female'? Crucially, what are the implications of gender and sexual fluidity and multiplicity for social policy, citizenship, new social movements and democracy? Gender Politics challenges ideas that we are all either male or female, and gay or straight. It explores the experiences of people who transgress these categories, and the social exclusion that they face. Surya Monro addresses topical debates concerning gender, and looks at different ways of theorising gender pluralism. She explains how gender and sexuality relate to other social characteristics such as 'race', class, and disability. As well as providing a way into some of the key academic discussions in the field of gender and sexuality, Gender Politics is also a tool for activists. Monro analyses the way in which mainstream citizenship, social policy, and democracy can -or cannot - be changed to reflect the needs of marginalised groups. She explores the social implications of equality for transgender, intersex, lesbian, gay and bisexual people, and assesses conflicts within these communities themselves.